(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The article considers an example of assembling a small-sized mobile robot. The main principles that distinguish a robot from other intelligent devices are considered. The types of parts that must be in each such robot are also given. The main stages of assembling a mobile robot are presented with photographs.